Japanese racial identities within US-Japan relations, 1853-1919 - Merida, Tarik (Edinburgh University Press, 2023)
Considers: Did race really matter? Racial ideology and political pragmatism in U.S.-Japan relationsBreaks up the traditional dichotomic view of race relationsEmploys a new and more functional theoretical approach to understand the negotiated quality of not only the Japanese racial identity, but also of racial identities in generalFirmly anchors Japanese history in a global frameworkIntroduces a wide array of new Japanese sources particularly on the topic of Japanese and African American relationsThis book retraces the process through which, at the turn of the twentieth century, the Japanese went from a racial anomaly to honorary members of the White race. It explores the interpretation of the Japanese race by Western powers, particularly the United States, during Japan’s ascension as a great power between 1853 and 1919. Forced to cope with this new element in the Far East, Western nations such as the U.S. had to device a negotiation zone in which they could accommodate the Japanese and negotiate their racial identity. In this book, Tarik Merida, presents a new tool to study this process of negotiation: the Racial Middle Ground
Keywords: Hochschulschrift; Geschichte 1853-1919; Rassismus; Ethnische Identität; Japan